INFLUENCE OF TA’AWUN (MUTUAL COOPERATION) AND SEJAHTERA LEADERSHIP IN SUSTAINING COMMUNITY ENGAGEMENT - Suhaimi M Mhd Sarif; Yusof Ismail; Rohaziah Yahya; Ashiqun Nabi (Journal of Islamic Management Studies, 2022)
Community engagement has increased partnership, unity and wealth sharing among community members in achieving sustainable development goals (SDGs). The surface engagement is not sustainable. A sustainable engagement is deeply rooted in the mind, soul, and attitude. Ta’awun (mutual cooperation) is spiritually driven cooperation in attaining al-birr (righteousness) and taqwa (piety). Sejahtera leadership integrates ‘ilm (knowledge), adab (manners), and amal (action) to lead oneself and others to achieve sustainability. The sustainable community agenda is no longer just a world forum agenda or academic debates. Key stakeholders are attracted to collaborating with civic organizations and institutions of higher learning. Every stakeholder is aligning with the seventeen (17) Sustainable Development Goals (SDGs). The institutions of higher learning are expected to incorporate community engagement agenda into the curriculum and co-curriculum. This paper postulated that ta’awun (mutual cooperation) and sejahtera leadership have significant effects on sustaining community engagement. Thus, this study explores the effect of ta’awun, sejahtera leadership, and the learning-by-doing theory in empowering students from institutions of higher learning to engage with the community. This paper outlines the process that student groups went through to formulate community engagement projects with SDG agenda. The community engagement projects have aligned with multiple SDG goals with the effect of ta’awun and sejahtera leadership. The study suggests education with action with the influence of ta’awun and sejahtera leadership. For future research, the study suggests all institutions of higher learning incorporate ta’awun and sejahtera leadership in all community engagement projects contributing to more sustainable planet earth.